STRUCTURE OF THE DIGITAL ECONOMY THROUGH THE PRISM OF THE THEORY OF MULTILEVEL COMPETITION - R. Yakubov (Вестник Северо-Кавказского федерального университета, 2022)
The article makes an attempt to consider the digital economy through the methodology of the theory of multilevel competition proposed by Professor S. G. Svetunkov. The problem of defining the traditional economy only as the production and distribution of products is highlighted, but the digital economy is based on demand. If there is a demand for digital technologies, there is production and there is distribution; if there is no demand, there is no need to develop production. Analyzing the structure of the digital economy as a sphere of human activity to meet human demand for various goods, the author proposes to consider the digital economy as one of the elements of the economy that is part of its infrastructure.